Analysis of hurricane extremes and record values in the Atlantic. Issue 2 (3rd April 2019) - Gulati, Sneh; George, Florence; Golam Kibria, B.M.
Abstract: People who live in the state of Florida recognize the impact of hurricanes have on their lives. With the hurricane season taking up 6 months of the year, Floridians feel that their lives are divided into two seasons; "the hurricane season" and the "calm season." Investigating hurricane risk is critical for the state of Florida; both from a socio-anthropological viewpoint and from an actuarial viewpoint. Using theory from record-breaking data, this article predicts the intensity of the next "big" storm and computes the probabilities of the waiting time for the future record. In addition to the prediction of future records, this article also considers the estimation of the extreme quantiles of the distribution of the intensities and presents a brief investigation into whether the occurrence of "intense" hurricanes is increasing.